Recent advances in the biosynthesis of polysaccharide-based antimicrobial glycoconjugate vaccines - Wang, Yuhui; Liu, Haodi; Wang, Baoying; Gheyret, Gülzire; Qin, Jingliang; Wang, Hanlin; Di, Yuhan; Wang, Yanling; Wang, Juan; Tan, Haining (Frontiers in Microbiology, 2025)
Glycoconjugate vaccines are a vital category of effective and safe commercial vaccines that have significantly reduced the global prevalence of drug-resistant bacterial infections. These vaccines are synthesized by covalently linking bacterial polysaccharide antigens to a carrier protein. Given that they produce a stronger and longer-lasting immune response than pure polysaccharides that activate only B cells, glycoconjugate vaccines have become one of the most promising vaccine types. However, the chemical synthesis of glycoconjugate vaccines is complex, costly, and labor-intensive. Therefore, the efficient preparation of biosynthetic glycoconjugates using microbial cell factories has emerged as a highly desirable manufacturing alternative. This review focuses on advancements in the recombinant microbial biosynthesis of glycoconjugate vaccines and summarizes various strategies to optimize their production. It is based on three key aspects: the selection of oligosaccharyltransferase (OST), the use of different vaccine carrier proteins, and the enhancement of key concentrations in the uridine diphosphate (UDP)-sugar supply. Finally, the review highlights technical challenges and discusses future directions for the recombinant synthesis of glycoconjugate vaccines.